2020
DOI: 10.1109/tsp.2020.3013781
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-Domain Signal Reconstruction Using $L_{p}$-Norm Regularization

Abstract: We focus on the generalized-interpolation problem. There, one reconstructs continuous-domain signals that honor discrete data constraints. This problem is infinite-dimensional and ill-posed. We make it well-posed by imposing that the solution balances data fidelity and some Lp-norm regularization. More specifically, we consider p ≥ 1 and the multi-order derivative regularization operator L = D N 0. We reformulate the regularized problem exactly as a finite-dimensional one by restricting the search space to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Therefore, the observation matrix X with the snapshots is T can be presented as It is noted that à is called the overcomplete dictionary and the number of à columns is much larger than that of rows. Similar to (8), it can be found that à not only depends spatial parameters but also depends polarization parameters. S is called sparse direction weights, each sparse weight has non-zero value only at the true source directions.…”
Section: D Sparse Signal Modelmentioning
confidence: 58%
“…Therefore, the observation matrix X with the snapshots is T can be presented as It is noted that à is called the overcomplete dictionary and the number of à columns is much larger than that of rows. Similar to (8), it can be found that à not only depends spatial parameters but also depends polarization parameters. S is called sparse direction weights, each sparse weight has non-zero value only at the true source directions.…”
Section: D Sparse Signal Modelmentioning
confidence: 58%
“…the vector of expansion coefficients d k has only a few nonzero entries. Such an assumption is exploited in [39]- [43] where the observed signals lie in the L-spline and B-spline spaces. However, in this paper, we assume the expansion coefficients d k are sparse in a certain transform domain Ψ ∈ R L×L .…”
Section: Generalization Of the Proposed Methods To Other Sampling Ker...mentioning
confidence: 99%
“…The theorem states that the signal can be recovered from M linear measurements, where M ≥ (Q + N 0 ) and N 0 is a spline order. Papers [40]- [43] rely on the main results of the method proposed in [39] and use grid-based discretization strategies that lead to convex optimization problems.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, placing electromagnetic vector antennas on multiple UAVs can constitute a new type of UAV swarm vector array. Several attempts, such as the application of p-norm (0 ≤ p ≤ 1) methods [21][22][23][24][25], orthogonal matching pursuit (OMP) methods [26,27], and the sparse Bayesian learning (SBL) methods [28][29][30][31], have aroused a lot of attention in DOA estimation. The essential idea of these algorithms is that the directions of incident sources are substantially sparse in the spatial domain, which is intrinsically different from the subspace-based algorithms.…”
Section: Introductionmentioning
confidence: 99%